2008
DOI: 10.4028/www.scientific.net/kem.368-372.849
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of C/SiC Composites Prepared at Low Temperatures

Abstract: 2D-C/SiC composites with high performance were prepared at temperatures as low as 900 °C. The flexural strength of the composites reached 329.61MPa, the same level as the composites prepared at 1200°C, and shear strength and fracture toughness were 32.14MPa and 14.65MPa·m1/2, respectively. The microstructure and mechanical properties of the composites after heat-treatment at 1600°C were also investigated to determine the potential applications at high temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…thrust chamber in rocket engines and thermal protection system in re-entry spacecrafts, due to their low density, high toughness and high oxidation resistance. 1,2 In many applications, the joining of C/SiC to metals is necessary to fabricate complex structural components.…”
Section: Introductionmentioning
confidence: 99%
“…thrust chamber in rocket engines and thermal protection system in re-entry spacecrafts, due to their low density, high toughness and high oxidation resistance. 1,2 In many applications, the joining of C/SiC to metals is necessary to fabricate complex structural components.…”
Section: Introductionmentioning
confidence: 99%
“…As structural materials for high temperature applications in atmosphere, the C/SiC composites must have excellent oxidation resistance [4][5][6]. In the literature [7,8], the mechanical properties and microstructure of C/SiC composites fabricated at low temperatures was investigated in depth, and the results showed that the C/SiC composite possessed outstanding performance. In order to adapt for application in oxidation environment as atmosphere, it is essential to study the oxidation resistance of C/SiC composites prepared at low temperatures.…”
Section: Introductionmentioning
confidence: 99%